Ratings of Perceived Exertion Misclassify Intensities for Sedentary Older Adults During Graded Cycling Test: Effect of Supramaximal High-Intensity Interval Training - Jabbour, Georges; Majed, Lina (Frontiers in Physiology, 2018)
The present study aims 1) to evaluate ratings of perceived exertion (RPE) and corresponding intensities during a maximal graded cycling test and 2) to determine the effects of 6 weeks of supramaximal cycling exercise (SCE) intervention on RPE and associated physiological factors in young and older sedentary groups. Two healthy groups of seventeen young adults [average (SD) age: 26.2 (2.4) year] and thirteen older adults [average (SD) age: 54.5 (2.3) year] completed a 6-week SCE intervention on an ergocycle. Physiological values and RPE were collected across stages corresponding to ventilator thresholds 1 (VT1) and 2 (VT2) of the graded cycling test and 10 minutes following the end of test and during the six bouts of SCE. The relative intensity for both VT1 and VT2 were also objectively calculated based on the percent of maximal heart rate %HRmax and peak oxygen consumption %V ̇O2peak. Before SCE intervention, RPE values were significantly higher for the older group compared to younger at VT1 [p<0.01] and VT2 [p<0.01], although both groups were working at similar relative intensities (%V ̇O2). After 6 weeks of SCE, the older group’s perceived effort values were normalized to the actual estimated ones and were similar to those observed in younger individuals. The intervention elicited physiological changes at rest and submaximal intensities, while no improvements were noted for both groups in aerobic fitness (i.e., V ̇O2peak). For both groups, RPE decreases with SCE at 10 minutes following graded test correlated significantly to V ̇O2 (r=0.61, p<0.01). Our study revealed that the initial over-estimation of the exertion levels found for the older sedentary group at the tested submaximal intensities was no longer present after 6 weeks of SCE training, therefore matching RPE values of the young group and those estimated by %HRmax and %V ̇O2peak methods. Therefore, combining the RPE method with other commonly used methods of estimating exercise intensity is highly recommended for sedentary older adults to suitably monitor the exercise intensity.